2022
DOI: 10.17305/bjbms.2021.6963
|View full text |Cite
|
Sign up to set email alerts
|

Impact of metabolic syndrome on the risk of endometrial cancer and the role of lifestyle in prevention

Abstract: Endometrial cancer is the second gynecological cancer with the highest global incidence. Among many associated risk factors, Among the risk factors, metabolic syndrome is an important and preventable one. It comprises a group of conditions that often occur together: central adiposity, hyperglycemia, arterial hypertension, and atherogenic dyslipidemia. This review aimed to describe the epidemiological and biological relationship between metabolic syndrome and endometrial cancer, focusing on the role of lifestyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 121 publications
0
7
0
Order By: Relevance
“…However, previous studies have mainly targeted limited lifestyle management, such as smoking, alcohol consumption, and exercise, and rarely considered emerging factors such as diet, sleep, social support, and sedentary behaviour [ 13 , 14 ]. Additionally, most studies on lifestyle management involving individuals with MetS have focused on CVD-related diseases [ 15 ] or site-specific cancers, such as endometrial cancer [ 16 ]. Research on all-cause and cause-specific mortality and the overall incidence of cancer are limited.…”
Section: Introductionmentioning
confidence: 99%
“…However, previous studies have mainly targeted limited lifestyle management, such as smoking, alcohol consumption, and exercise, and rarely considered emerging factors such as diet, sleep, social support, and sedentary behaviour [ 13 , 14 ]. Additionally, most studies on lifestyle management involving individuals with MetS have focused on CVD-related diseases [ 15 ] or site-specific cancers, such as endometrial cancer [ 16 ]. Research on all-cause and cause-specific mortality and the overall incidence of cancer are limited.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous factors are at the very core of the development of EC (in particular endometrioid subtype), including obesity, early menarche, late menopause, nulliparity, unopposed estrogen therapy, and chronic anovulation. A temporal pattern association has been described and coincides with a parallel increase in obesity and the prevalence of metabolic syndrome (MetS) observed in the general population [1,2].…”
Section: Introductionmentioning
confidence: 57%
“…Studies show a significantly higher prevalence of metabolic disorders following surgical menopause compared to natural menopause. This association is linked to the sudden decline in estrogen levels caused by surgery, which can lead to endothelial dysfunction, dyslipidemia [1,[26][27][28][29], and increased risk of cardiovascular events [30][31][32][33][34]. Research suggests a 1.5-fold to 9.7-fold increased risk of MetS in women who undergo surgical menopause compared to natural menopause [1,[35][36][37][38][39].…”
Section: Surgical Menopause and Increased Mets Riskmentioning
confidence: 99%
“…Metabolic diseases, including obesity (body mass index (BMI) > 30 kg/m 2 ), and diabetes mellitus (DM), belong to the most important contributing factors for the rising rates (Raglan et al 2019 ). Although unopposed estrogen exposure is considered a major driver of endometrial carcinogenesis, other additional factors such as chronic inflammation, insulin resistance, and hyperinsulinemia are allied to substantial risk factors for EC (Perez-Martin et al 2022 ; Siegel et al 2021 ). Previous epidemiological studies revealed that obesity, DM, and metabolic syndrome (MetS) are each linked to an increase in EC incidence, but their separate and combined influence on survival remains unclear (Raglan et al 2019 ; Perez-Martin et al 2022 ; Romanos-Nanclares et al 2023 ; Morice et al 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although unopposed estrogen exposure is considered a major driver of endometrial carcinogenesis, other additional factors such as chronic inflammation, insulin resistance, and hyperinsulinemia are allied to substantial risk factors for EC (Perez-Martin et al 2022 ; Siegel et al 2021 ). Previous epidemiological studies revealed that obesity, DM, and metabolic syndrome (MetS) are each linked to an increase in EC incidence, but their separate and combined influence on survival remains unclear (Raglan et al 2019 ; Perez-Martin et al 2022 ; Romanos-Nanclares et al 2023 ; Morice et al 2016 ). Conversely, Tang et al described in a meta-analysis the perceived protective effects of metformin intake leading to a decrease in incidence rates and an improvement in OS in EC Patients.…”
Section: Introductionmentioning
confidence: 99%